2019
DOI: 10.1002/bmc.4492
|View full text |Cite
|
Sign up to set email alerts
|

Buprofezin dissipation and safety assessment in open field cabbage and cauliflower using GC/ITMS employing an analyte protectant

Abstract: An analytical method for the determination of buprofezin residues in cabbage and cauliflower was developed and validated using gas chromatography with ion trap mass spectrometry. The analyte protectant D-sorbitol was used at a concentration level of 0.5 mg mL −1 in acetonitrile instead of in matrix for constructing the calibration curves of the buprofezin standard. The average recoveries ranged from 91.3 to 96.8%, with an RSD of ≤2.7%. The limits of detection and quantitation of the method in cabbage and cauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For buprofezin, the studies on plants and soil were limited and its persistence behaviour was found varying with various crops (Mohapatra et al 2020). In a study, the half-lives of buprofezin in cabbage were estimated as 1.73 and 1.85 days for SD and DD respectively; and for cauli ower, these values were 2.1 and 2.36 days for SD and DD respectively (Abdallah et al 2019). In our case, the half-lives were slightly lower than those earlier reports.…”
Section: Dissipation Kinetics and Waiting Periodsmentioning
confidence: 99%
“…For buprofezin, the studies on plants and soil were limited and its persistence behaviour was found varying with various crops (Mohapatra et al 2020). In a study, the half-lives of buprofezin in cabbage were estimated as 1.73 and 1.85 days for SD and DD respectively; and for cauli ower, these values were 2.1 and 2.36 days for SD and DD respectively (Abdallah et al 2019). In our case, the half-lives were slightly lower than those earlier reports.…”
Section: Dissipation Kinetics and Waiting Periodsmentioning
confidence: 99%
“…Nihon Nohyaku Co., Ltd. (Tokyo, Japan) developed buprofezin for registration in 1983, 1 which is an insect growth regulator (IGR). 1 Its chemical formula is C 16 H 23 N 3 SO, and its relative molecular weight is 305.4.…”
Section: Introductionmentioning
confidence: 99%
“…Nihon Nohyaku Co., Ltd. (Tokyo, Japan) developed buprofezin for registration in 1983, 1 which is an insect growth regulator (IGR). 1 Its chemical formula is C 16 H 23 N 3 SO, and its relative molecular weight is 305.4. The substance is a white crystal with a melting point of 104.5−105.5 °C and a relative density of 1.18 (25 °C), and it is stable under conditions of acid, alkali, light, and heat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissipation of pesticides is influenced by several factors, including the plant species, plant growth (dilution), climate (rainfall, sunlight, temperature, etc. ), pesticide application method, plant uptake of the pesticide (via leaves, stem, or roots), and properties of the pesticide (Abdallah, El Agamy, et al, 2019;Abdallah, El-Hamid, & Raheem, 2019;Abdallah & Malhat, 2020). The dissipation behavior of myclobutanil, penconazole, triadimenol, and tebuconazole has been investigated individually in various crops under specific climate conditions and cultivation techniques (Abd-Alrahman & Ahmed, 2012;Abd-Alrahman & Ahmed, 2013;Abdella et al, 2015;Cui et al, 2011;Deng et al, 2010;Dong et al, 2010;Dong & Hu, 2014;Dubey et al, 2020;Hassan et al, 2013;Heshmati et al, 2020;Kaur et al, 2012;Liu et al, 2009;Liu et al, 2012;Lou et al, 2008;Lucini & Molinari, 2009;Matadha et al, 2019;Romeh et al, 2009;Saidi et al, 2017;Singh & Singh, 2014).…”
mentioning
confidence: 99%